Answer :

(i) By using the distributive law

= a(a + 5) +3((a+5)


= a2 +5a +3a +15


= a2 +8a +15


(ii) By using the distributive law


= 3t (3t + 4) + 1(3t + 4)


= 9t2 + 12t +3t + 4


= 9t2 + 15t +4


(iii) By using the distributive law


= a( a+2) –8(a+2)


= a2 + 2a – 8a – 16


= a2 – 6a –16


(iv) By using the distributive law


= a (a–2) – 6 ( a – 2)


= a2 –2a – 6a +12


= a2 – 8a +12


Rate this question :

How useful is this solution?
We strive to provide quality solutions. Please rate us to serve you better.
Try our Mini CourseMaster Important Topics in 7 DaysLearn from IITians, NITians, Doctors & Academic Experts
Dedicated counsellor for each student
24X7 Doubt Resolution
Daily Report Card
Detailed Performance Evaluation
caricature
view all courses
RELATED QUESTIONS :

Find the product:Karnataka Board - Mathematics Part I

Simplify the follKarnataka Board - Mathematics Part I